2021
DOI: 10.1108/wje-08-2020-0334
|View full text |Cite
|
Sign up to set email alerts
|

The effect of clam shell powder on kinetics of water absorption of jute epoxy composite

Abstract: Purpose Here, attempts have been made to explore the possible use of Marine waste as filler materials into the bio-fibre composites. Clam shell is a type of marine waste which belongs to the class of Bivalvia. It is mainly made of aragonite crystalline polymorphs. This paper aims to develop a new class of natural fibre composite in which jute fibre as reinforcement, epoxy as matrix and clam shell, as particulate microsphere filler. The study investigates the effects of different amounts of clam shell powder on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The composites achieved moisture content equilibrium only when they gained less than 0.01% in weight daily. Under equilibrium conditions, the absorbed water is known as free water and does not cause any dimensional changes ( h m ) 33 . Figure 7 depicts the correlation between the h m and duration of immersion in (a) distilled water (pH 7), (b) seawater (pH 8), and (c) the acidic solution (pH 3).…”
Section: Resultsmentioning
confidence: 99%
“…The composites achieved moisture content equilibrium only when they gained less than 0.01% in weight daily. Under equilibrium conditions, the absorbed water is known as free water and does not cause any dimensional changes ( h m ) 33 . Figure 7 depicts the correlation between the h m and duration of immersion in (a) distilled water (pH 7), (b) seawater (pH 8), and (c) the acidic solution (pH 3).…”
Section: Resultsmentioning
confidence: 99%
“…Equilibrium moisture content was reached when the daily weight gain of the sample was less than 0.01%. Under equilibrium conditions, the absorbed water is known as free water and does not cause any dimensional changes [35]. The 5.…”
Section: Tablementioning
confidence: 99%
“…The TGA results revealed that the thermal stability of the composites increased with addition of CaCO 3 nanoparticles. Jena et al [ 9 ] studied the effect of clam shell on jute fiber reinforced epoxy composites. Clam shell is mainly composed of CaCO 3 particles.…”
Section: Introductionmentioning
confidence: 99%